Grito rock : movimento de contracultura no cenário de música autoral em Cuiabá - Kobayashi, Juliana Sayumi (2013)
This work aims to elucidate questions concerning the Grito Rock Festival, a counterculture event that appears in a movement of the new youthful cultures in opposition to the carnival hegemony, and promotes a thought rupture to consider new forms of making and thinking culture. The studies of the cultural phenomenon, in simplified way, could be explained as the study of the social-historic world constituted as a field of meanings including many questions such as action; expressions; verbal and non-verbal manifestations (symbols, artifacts, etc.); how the individual manifests trough these forms of expression, understands himself and others through the interpretation of the expressions he produces, and also from the ones he receives inside a social and historical context. To study the cultural phenomenon of the Grito Rock, it is necessary to elucidate the theories, concepts and the contextualization of the event the way it is possible to categorize this phenomenon in the theories, and thus to raise notes and considerations about the relevance of this event for the studies of the culture in the state of Mato Grosso.